Improving Brand Loyalty Through Celebrity Influencer’s Credibility, Attractiveness, Online Customer Reviews and Brand Satisfaction as Mediating - Anggitasari, Oktavia Diyah; Kuswati, Rini (Jurnal Economic Resource, 2025)
This study investigates the impact of internet consumer evaluations, celebrity influencers' reputation, and their beauty on brand loyalty, mediated by brand satisfaction. Using a quantitative method with PLS-SEM analysis, 150 Wardah consumers who follow Raline Shah on social media participated in this research. The results reveal that all three variables significantly affect brand satisfaction, which in turn strongly influences brand loyalty. Additionally, the link between loyalty, online reviews, and influencer traits is mediated by brand satisfaction. The findings highlight the importance of credible and attractive endorsers, as well as positive customer reviews, in building lasting brand relationships in the beauty industry.